Sexual politics in Ian McEwan's The Innocent - Abbasiyannejad, Mina; Talif, Rosli; Lalbakhsh, Pedram (American-Eurasian Network for Scientific Information, 2013)
Rape and sexual abuse as a global conflict has always been an inevitable part of war, used as a tactic both for humiliation and domination. Recent studies show that despite several attempts to stop sexual torture as the consequences of war it is an ongoing process in every part of the world. This necessitates an urgent solution for this epidemic problem. As a contemporary author, in his The Innocent, McEwan reflects this universal problem and presents the sexual relationships within war circumstances. His well known novel is set in the middle of Cold War and portrays sexual relationship between Leonard and Maria. Leonard’s process of transformation from an ordinary person to a real conqueror of the Second World War is investigated to show how war can change individual’s attitude toward human. This study is a critical analysis of The Innocent in the light of Kate Millett’s theory of sexual politics. Millett explicates that sex has political implications, and that it is always under the influence of border issues in the society. By politics she means power-structured relationships between male and female. It reveals the impact of war circumstances on the individual’s personality and investigates how wars can change people. This study highlights that as a result of war Leonard, a naïve, innocent, and harmless character of the story transforms to a brutal sexual predator, and acts like any other victor soldiers to dominate and sexually torture women from the defeated country. The findings of the study demonstrate that McEwan’s emphasis on war and its destructive effects on civilians, especially women, is his call to invite the world look at wars in a new and different way. Such understanding and demonstration of the bitter condition of women at wartime foregrounds the dire need for certain effective law to prevent sexual crimes and violence that target women during wartime.